A study to assess feedback of patients who received benefit of Rajeev Gandhi Jeevandayi Arogya Yojana during first year of phase I in a private tertiary care network hospital in Maharashtra - Katke, Praveen H.; Wadke, Rishikesh A.; Waigankar, Prasad J. (International Journal Of Community Medicine And Public Health, 2018)
Background:Rajeev Gandhi Jeevandayi Arogya Yojana (RGJAY) is a government initiated cashless Health Insurance Scheme. The scheme’s objective is to improve health care access through an identified network of health care providers. MGM Medical College is one of the network hospitals in Raigad District of Maharashtra, India. This study is aimed at assessing feedback of patients who received benefit of this scheme. Methods:A total of 884 pre-authorizations were approved during the study period. As a 10 percent random sample, feedback letters received were analyzed for 91 patients. The responses obtained were in local language. Telephonic validations were done wherever needed. Response categories were standardized and coded. Analysis was done using Epi-info software. Results:Complete improvement in ailment was felt by 76 (83.5%) respondents while 12 (13.2%) mentioned partial improvement. Though all patients felt that scheme should continue, 37 (40.7%) said they had faced issues related to scheme. If free treatment would not have been received under the scheme, a majority of patients (56%) felt they would have succumbed to their illness while 32 (35.2%) patient had thought of selling their assets or taking loan for covering treatment expenses. Only 5 (5.5%) patients said they would have gone to Government or Charitable hospital in absence of the scheme. Conclusions:The scheme acts as an important social security measure as many poor patients would not have sought medical treatment in absence of this scheme. However there is a scope for improvement to reduce the hurdles for better scheme utilization.